Differential cardiovascular benefits of SGLT2 inhibitors, sacubitril/valsartan, omecamtiv mecarbil, and vericiguat across heart failure phenotypes: a systematic review and meta-analysis - Wang, Meng; Zuo, Zhihong; Wu, Ting; Zhou, Zijing (Frontiers in Pharmacology, 2026)
AimThe study evaluated the cardiovascular outcomes associated with pharmacological treatments in heart failure (HF) patients and explored whether the benefits/risks associated with these drugs for HF with mildly reduced or preserved ejection fraction (HFmrEF/HFpEF) were consistent with HF with reduced EF (HFrEF).MethodsSeveral online databases were searched. All studies explored the cardiovascular effects of sodium glucose cotransporter-2 inhibitor (SGLT2i), sacubitril/valsartan, omecamtiv mecarbil and vericiguat were screened and reviewed.ResultsA total of 39 studies were included. Compared with placebo therapy, SGLT2i significantly reduced cardiovascular death and hospitalization for HF (HHF) in both HFrEF and HFmrEF/HFpEF patients (approximately 13%–27% risk reduction). SGLT2i reduced serious adverse events across all HF types. Sacubitril/valsartan demonstrated significant benefits in HFrEF patients, reducing cardiovascular death by 19%, all-cause mortality by 22%, and HHF by 22%. However, these benefits were not observed in HFmrEF/HFpEF patients. In contrast, sacubitril/valsartan substantially increased hypotension risk in HFmrEF/HFpEF patients. Omecamtiv mecarbil and vericiguat tended to improve cardiovascular outcomes in patients with HF, but the difference was not statistically significant.ConclusionSGLT2i represents an effective and safe treatment strategy across the HF spectrum. Sacubitril/valsartan significantly improves outcomes in HFrEF but requires careful benefit-risk evaluation in HFmrEF/HFpEF patients. Current evidence does not support routine use of omecamtiv mecarbil or vericiguat. Large-scale randomized trials are warranted to validate these findings.Systematic review registrationCRD42023455966.